Advancements in Cyclostationary Technique for Cognitive Radio: An In-Depth Examination and Evaluation - Charkha, Sarita; Jakhete, Mayur; Waghmare, Prachi; Chaudhari, Dipamala; Jatale, Ketan; Zope, Tejaswini; Rathi, Bhushan; Sharma, Vidur (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In contemporary society, information communication has reached unprecedented levels, connecting individuals at all strata, from grassroots to the highest echelons. The integration of information technology and communication has become an intrinsic part of everyday life, catering to knowledge-based, entertainment-based, economical-based, and social-based data. As the volume of information data continues to grow, Information Communication Technology (ICT) plays a pivotal role in the lives of common individuals. However, the surge in users is met with the challenge of limited resources, specifically channel bandwidth for communication. This paper addresses the issue of communication channel utilization in the face of a rising number of users. To optimize and accommodate an increasing user base within the constraints of available channels, the proposed system introduces the Enhanced Cyclostationary technique for Cognitive Radio. This innovative approach aims to maximize the efficiency of communication channels, ensuring reliable connectivity for the expanding user population.